Battery cell, preparation method of battery cell, soft package lithium ion battery and application of soft package lithium ion battery
By using modified nickel-cobalt lithium manganate, nano-silicon-based anode material and specific separators in lithium-ion batteries, combined with electrolyte with good low temperature and safer, the deterioration and safety of lithium-ion batteries under low temperature conditions is solved. The problem of low performance achieves efficient low-temperature discharge and long cycle life.
Patent Information
- Application Number
- CN202310973022.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-03
AI Technical Summary
Existing lithium-ion batteries have deteriorated discharge performance under low temperature conditions and are low in safety, making it difficult to meet the applications that require high and low temperature adaptability such as emergency rescue and medical electronics.
Modified nickel-cobalt lithium manganate as the positive electrode material, nano-silicon-based anode material and PVDF-coated PE/PP/PE separator, combined with low temperature and better safety electrolyte, form an efficient soft-pack lithium-ion battery .
It significantly improves the low-temperature discharge performance and cycle stability of the battery, enhances the safety performance of the battery, and can maintain the discharge capacity by more than 60% under -40℃, and the capacity retention rate reaches more than 90% after 500 weeks of cycle.
Smart Images

Figure CN119447207A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of low-temperature mobile power sources, and in particular to a battery cell and a preparation method thereof, a soft-package lithium-ion battery and applications thereof. Background Art
[0002] In recent years, the global economy has maintained a high-speed development trend. The direct consequence of the rapid development of manufacturing industry and the rapid increase in population is the destruction of the global environment and the more obvious energy crisis. As an important part of the new energy field, the battery industry is bound to become a hot spot in the development of the global economy.
[0003] Lithium-ion batteries are widely used due to their high operating voltage, high specific energy, and large capacity. However, the operating temperature range is one of the important performance indicators of lithium-ion batteries. The operating temperature range of conventional consumer batteries from -20°C to 60°C cannot fully meet people's needs. For example, emergency rescue, medical electronics, robots, aerospace equipment, etc. need to adapt to the large temperature differences caused by regions and seasons, and even need to have good low-temperature discharge performance after long-term low-temperature storage.
[0004] When the temperature of current lithium-ion batteries is too low, the conductivity will be greatly reduced, the impedance of the SEI film will increase sharply, and the impedance of lithium ions in the electrode will also increase accordingly; when the temperature is high, the oxidation activity of the positive electrode material is high, the side reaction between the electrode and the electrolyte is intensified, and the transition metal is continuously dissolved into the electrode surface and deposited on the surface, which increases the internal resistance and thickens the battery, further affecting its low-temperature performance. In addition, excessive impedance will also cause lithium dendrites to form on the surface of the negative electrode, which will cause safety problems. The adaptability of battery size to equipment is also a practical application indicator that cannot be ignored. In terms of battery pack assembly, soft-pack batteries have stronger design flexibility in external dimensions than cylindrical batteries. Therefore, it is urgent to develop a low-temperature soft-pack lithium-ion battery with good cycle performance, good low-temperature discharge performance after low-temperature storage, and high safety. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems in the prior art that the low-temperature discharge performance deteriorates after long-term low-temperature storage and the safety is low, and to provide a battery cell and a preparation method thereof, a soft-pack lithium-ion battery and applications thereof.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a battery cell, which comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein:
[0007] The positive electrode sheet comprises modified nickel cobalt manganese oxide, and the modified nickel cobalt manganese oxide comprises core-shell type nickel cobalt manganese oxide and a boron-containing compound coated on the surface of the core-shell type nickel cobalt manganese oxide; wherein the content of nickel element in the core-shell type nickel cobalt manganese oxide is gradually reduced from the inside to the outside, the content of cobalt element is evenly distributed from the inside to the outside, and the content of manganese element is gradually increased from the inside to the outside;
[0008] The negative electrode sheet comprises a nano-silicon-based negative electrode material, which is a mixture of a silicon-oxygen material and graphite; wherein, based on the total weight of the nano-silicon-based negative electrode material, the content of the graphite is 82-88wt%; the silicon-oxygen material comprises silicon oxide and a carbon coating layer coated on the surface of the silicon oxide, and the silicon oxide comprises a SiO2 matrix and nano-silicon crystal particles uniformly distributed in the SiO2 matrix.
[0009] The second aspect of the present invention provides a method for preparing a battery cell, the method comprising: winding a positive electrode sheet, a negative electrode sheet and a separator into an electrode group, and injecting an electrolyte to prepare the battery cell; wherein,
[0010] The positive electrode sheet comprises modified nickel cobalt manganese oxide, wherein the modified nickel cobalt manganese oxide comprises core-shell type nickel cobalt manganese oxide and a boron-containing compound coated on the surface of the core-shell type nickel cobalt manganese oxide, wherein the content of nickel in the core-shell type nickel cobalt manganese oxide gradually decreases from the inside to the outside, the content of cobalt is evenly distributed from the inside to the outside, and the content of manganese increases from the inside to the outside;
[0011] The negative electrode sheet comprises a nano-silicon-based negative electrode material, which is a mixture of a silicon-oxygen material and graphite; wherein, based on the total weight of the nano-silicon-based negative electrode material, the content of the graphite is 82-88wt%; the silicon-oxygen material comprises silicon oxide and a carbon coating layer coated on the surface of the silicon oxide, and the silicon oxide comprises a SiO2 matrix and nano-silicon crystal particles uniformly distributed in the SiO2 matrix.
[0012] A third aspect of the present invention provides a battery cell prepared by the preparation method provided by the present invention.
[0013] A fourth aspect of the present invention provides a soft-pack lithium-ion battery, the battery comprising the battery cell provided by the present invention.
[0014] A fifth aspect of the present invention provides an application of the soft-pack lithium-ion battery provided by the present invention as a low-temperature mobile power source.
[0015] Through the above technical solution, the beneficial effects of the present invention are:
[0016] The active material of the positive electrode sheet of the present invention adopts a core-shell type nickel cobalt manganese oxide positive electrode material coated with a boron element. The core of the core-shell type nickel cobalt manganese oxide has a high nickel content and an outer layer has a high manganese content. The active material of the negative electrode sheet adopts a nano-silicon-based negative electrode material obtained by mixing silicon oxide material and graphite. The two cooperate with each other to improve the cycle stability and safety performance of the soft-pack lithium-ion battery.
[0017] In a preferred embodiment of the present invention, the active material of the positive electrode sheet adopts a core-shell type nickel cobalt manganese oxide positive electrode material coated with boron element, the active material of the negative electrode sheet adopts a nano-silicon-based negative electrode material, the diaphragm adopts a PVDF-coated PE / PP / PE diaphragm, and the electrolyte adopts a low-temperature and safe electrolyte. This specific combination of materials greatly improves the low-temperature performance and safety performance of the battery.
[0018] Furthermore, when preparing positive and negative electrode sheets, by selecting core-shell type nickel cobalt manganese oxide of suitable type and structure for boron coating as the active material of the positive electrode sheet, selecting nano silicon-based negative electrode material of suitable composition and structure as the active material of the negative electrode sheet, selecting suitable coating amount of boron element, particle size and specific surface area of modified nickel cobalt manganese oxide, graphite content, particle size and specific surface area of nano silicon-based negative electrode material, coating amount and slurry composition of positive and negative electrode slurry, thickness and compaction density of positive and negative electrode sheets; when preparing the diaphragm, selecting suitable diaphragm thickness and covering thickness of polyvinylidene fluoride, selecting suitable type and proportion of solvent and additive when preparing the electrolyte, the low temperature and safety performance of the battery are further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 1 is a low-temperature discharge curve diagram of the soft-pack lithium-ion batteries prepared in Example 1 of the present invention and Comparative Examples 1-3;
[0020] Figure 2 It is a normal temperature 0.5C cycle curve diagram of the soft-pack lithium-ion batteries prepared in Example 1 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] The first aspect of the present invention provides a battery cell, which comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein:
[0023] The positive electrode sheet comprises modified nickel cobalt manganese oxide, and the modified nickel cobalt manganese oxide comprises core-shell type nickel cobalt manganese oxide and a boron-containing compound coated on the surface of the core-shell type nickel cobalt manganese oxide; wherein the content of nickel element in the core-shell type nickel cobalt manganese oxide is gradually reduced from the inside to the outside, the content of cobalt element is evenly distributed from the inside to the outside, and the content of manganese element is gradually increased from the inside to the outside;
[0024] The negative electrode sheet comprises a nano-silicon-based negative electrode material, which is a mixture of a silicon-oxygen material and graphite; wherein, based on the total weight of the nano-silicon-based negative electrode material, the content of the graphite is 82-88wt%; the silicon-oxygen material comprises silicon oxide and a carbon coating layer coated on the surface of the silicon oxide, and the silicon oxide comprises a SiO2 matrix and nano-silicon crystal particles uniformly distributed in the SiO2 matrix.
[0025] In the present invention, the content of nickel in the core-shell type nickel cobalt manganese oxide is distributed in a gradually decreasing manner from the inside to the outside, the content of cobalt is evenly distributed from the inside to the outside, and the content of manganese is distributed in a gradually increasing manner from the inside to the outside, which means that based on the total weight of nickel, cobalt and manganese in the core-shell type nickel cobalt manganese oxide, in the core-shell type nickel cobalt manganese oxide, the mass percentage of nickel is distributed in a gradually decreasing manner from the inside to the outside, the mass percentage of cobalt is evenly distributed from the inside to the outside, and the mass percentage of manganese is distributed in a gradually increasing manner from the inside to the outside.
[0026] The core-shell type of lithium nickel cobalt manganese oxide in the positive electrode sheet has high nickel in the core and high manganese in the outer layer. It has high structural stability, which is beneficial to the improvement of the overall cycle stability and safety performance of the positive electrode material, making the nickel content in the core higher and the manganese content in the outer shell higher, which is more conducive to the improvement of battery energy density and surface stability. Boron coating, on the one hand, can effectively inhibit the precipitation of lattice oxygen during the electrochemical reaction by utilizing the strong B=O bond energy, and reduce the capacity loss caused by irreversible phase change. On the other hand, the high lithium ion conductor Li2O-B2O3 coating layer can stabilize the electrode-electrolyte interface to a certain extent, thereby further improving its cycle stability.
[0027] The nano-silicon-based negative electrode material in the negative electrode sheet is a mixture of carbon-coated silicon oxide and graphite materials. The volume expansion of the silicon oxide negative electrode filled with nano-silicon crystal particles is small, which reduces the impact of the silicon volume effect on the electrode sheet, and inactive substances such as Li2O are produced during the charge and discharge process. The Li2O matrix can act as a fast diffusion channel for lithium ions, making it better in terms of cycle and rate performance when lithium is inserted. The content of graphite should not be too much or too little. Too much will not meet the needs of high-energy density batteries in real environments, and too little will cause the problem of negative electrode expansion to be very prominent.
[0028] According to the present invention, nano silicon crystal particles in silicon oxide are uniformly distributed in a SiO2 matrix, and then carbon is coated on the surface of the obtained silicon oxide, and then the obtained silicon oxide material and graphite are mixed to obtain a nano silicon-based negative electrode material. In the present invention, the silicon oxide material can be obtained by self-production or commercially available, for example, it can be purchased from Shanghai Shanshan Technology Co., Ltd.
[0029] According to the present invention, preferably, based on the total weight of nickel, cobalt and manganese in the core-shell type nickel cobalt manganese oxide, the change rate of the nickel content from the core to the core surface of the core-shell type nickel cobalt manganese oxide is 3-5wt% / μm, and the change rate of the manganese content is 3-5wt% / μm;
[0030] From the core surface to the shell surface of the core-shell type nickel cobalt manganese lithium oxide, the change rate of the nickel content is 5-6wt% / μm, and the change rate of the manganese content is 5-6wt% / μm.
[0031] According to the present invention, preferably, the distance from the core to the core surface of the core-shell type lithium nickel cobalt manganese oxide is 2.7-3.2 μm, and the distance from the core surface to the shell surface is 1.5-2.5 μm.
[0032] The nickel element and the manganese element are both distributed in a double gradient concentration from the inside to the outside, that is, the nickel element content from the center of the core-shell type nickel cobalt manganese oxide particle to 2.7-3.2 μm from the center decreases slightly, with a change rate of 3-5 wt% / μm, and the nickel element content from 2.7-3.2 μm from the center of the particle to the outer surface of the particle decreases significantly, with a change rate of 5-6 wt% / μm; the manganese element content from the center of the core-shell type nickel cobalt manganese oxide particle to 2.7-3.2 μm from the center increases slightly, with a change rate of The rate is 3-5wt% / μm, while the manganese content increases greatly from 2.7-3.2μm from the center of the particle to the outer surface of the particle, with a change rate of 5-6wt% / μm, so that the concentration of transition metal ions (nickel ions and manganese ions) has two different distribution gradients, and the concentration gradient change occurs at 2.7-3.2μm from the center of the particle. This material has a higher nickel content in the interior, which is more conducive to obtaining and maintaining high capacity, and has a higher manganese content in the outer layer, which is more conducive to improving cycle stability and thermal stability.
[0033] According to the present invention, preferably, based on the total weight of nickel, cobalt and manganese in the core-shell type nickel cobalt manganese oxide, the contents of nickel at the core, at the core surface and at the shell surface of the core-shell type nickel cobalt manganese oxide are 75-85wt%, 67-73wt% and 47-62wt%, respectively.
[0034] According to the present invention, preferably, based on the total weight of nickel, cobalt and manganese in the core-shell type nickel cobalt manganese oxide, the contents of manganese at the core, core surface and shell surface of the core-shell type nickel cobalt manganese oxide are 5-18wt%, 17-26wt% and 28-46wt%, respectively.
[0035] According to the present invention, preferably, based on the total weight of nickel, cobalt and manganese in the core-shell type nickel cobalt manganese oxide, the content of cobalt in the core, core surface and shell surface of the core-shell type nickel cobalt manganese oxide is 7-10wt%.
[0036] In the present invention, a point can be taken at any core surface of the core-shell type nickel cobalt manganese lithium, and the element content at the core surface of the core-shell type nickel cobalt manganese lithium can be obtained by measuring the element mass percentage at the point; similarly, a point can be taken at any shell surface of the core-shell type nickel cobalt manganese lithium, and the element content at the shell surface of the core-shell type nickel cobalt manganese lithium can be obtained by measuring the element mass percentage at the point. Comparing the results obtained by analysis at different points, it is proved that the content distribution of nickel, cobalt and manganese in the core-shell type nickel cobalt manganese lithium provided by the present invention satisfies that the content of nickel element is gradually reduced from the inside to the outside, the content of cobalt element is evenly distributed from the inside to the outside, and the content of manganese element is gradually increased from the inside to the outside.
[0037] According to the present invention, preferably, the boron-containing compound is selected from at least one of boron trioxide, boron trichloride, boron trifluoride, boric acid and sodium metaborate.
[0038] According to the present invention, preferably, based on the total weight of the modified lithium nickel cobalt manganese oxide, the content of boron in the boron-containing compound is 2-12wt%. The content of boron in this range can better optimize the electrical performance and safety performance, but should not be too high or too low. If it is too high, unreduced B2O3 will remain on the surface of the material, which will increase the impedance. If it is too low, the coating will be incomplete and the modification will not be obvious.
[0039] According to the present invention, preferably, the D of the modified lithium nickel cobalt manganese oxide 50 The particle size is 8-12μm and the specific surface area is 0.5-2m 2 / g. When the particle size and specific surface area are within this range, the battery can have a high volume energy density and good low-temperature charge and discharge performance. If the particle size is too large, the specific surface area is small, the adsorption of the particles is relatively poor, and the positive electrode active material may be separated from the matrix and free in the electrolyte. Once it comes into contact with the negative electrode material, it will cause a local battery short circuit; if the particle size is too small, the specific surface area is too large, the powder is easy to agglomerate, and it is difficult to disperse in the organic solvent, the active material of the electrode sheet is unevenly distributed, and the battery performance is not reduced; at the same time, if the particle size is too fine, it is easy to cause surface defects, induce battery polarization, and reduce the electrochemical energy of the positive electrode.
[0040] In the present invention, the modified lithium nickel cobalt manganese oxide can be obtained by self-production or commercially available, for example, from GEM New Materials Company.
[0041] According to the present invention, preferably, the D of the nano silicon-based negative electrode material 50 The particle size is 7-13μm and the specific surface area is 5-9m 2 / g. The particle size and specific surface area within this range can meet the requirement of lower impedance at a higher unit load, improve the utilization rate of active materials, and alleviate the huge volume change and cycle deterioration of silicon during lithium insertion and extraction. If the particle size is too large, the specific surface area will be too large, which will cause a large area of SEI film to be produced in the electrode during the first lithium insertion, thereby consuming lithium ions in the battery, and the silicon particles inside the larger particle size are prone to cracking during the cycle, which reduces the electrical contact activity between materials, while too small a particle size will deteriorate its oxidation resistance and dispersibility, and aggravate the occurrence of side reactions on the electrode surface.
[0042] According to the present invention, preferably, in the nano-silicon-based negative electrode material, the gram capacity of the graphite is 300-360 mA·h / g. The gram capacity of the graphite within this range can ensure that when the ratio of the graphite to the silicon-oxygen negative electrode material is 82-88wt%, it has a better compaction density and cycle stability.
[0043] According to the present invention, preferably, the graphite is selected from at least one of artificial graphite, natural graphite and mesophase carbon microbeads.
[0044] According to the present invention, preferably, in the nano-silicon-based negative electrode material, the gram capacity of the silicon-oxygen material is 1250-1750 mA·h / g.
[0045] According to the present invention, preferably, the average particle size of the nano-silicon crystal particles is 2-10 nm, and the average particle size of the SiO2 matrix is 3-8 μm.
[0046] According to the present invention, preferably, based on the total weight of the silicon-oxygen material, the content of the nano-silicon crystal particles is 26-28wt%, and the content of the SiO2 matrix is 69-73wt%. The contents of the nano-silicon crystal particles and the SiO2 matrix meet this range, which can ensure good cycle stability.
[0047] According to the present invention, preferably, the carbon coating layer is amorphous carbon.
[0048] According to the present invention, preferably, the thickness of the carbon coating layer is 8-13 nm. Carbon coating with amorphous carbon, and the nano-silicon particle size and the thickness of the carbon coating layer are within this range, can ensure good cycle stability and low temperature performance.
[0049] According to the present invention, preferably, the positive electrode sheet is obtained by coating the positive electrode slurry including the modified nickel cobalt lithium manganese oxide on the surface of the positive electrode collector, and the negative electrode sheet is obtained by coating the negative electrode slurry including the nano silicon-based negative electrode material on the surface of the negative electrode collector.
[0050] According to the present invention, preferably, the positive electrode current collector is aluminum foil, preferably with a thickness of 12-16 μm; the negative electrode current collector is copper foil, preferably with a thickness of 6-10 μm.
[0051] According to the present invention, preferably, the surface density of the positive electrode slurry coated on the surface of the positive electrode current collector is 110-130 g / cm 2 .
[0052] According to the present invention, preferably, the surface density of the negative electrode slurry coated on the surface of the negative electrode current collector is 70-80 g / cm 2 .
[0053] The surface density of the positive and negative electrode slurry coating is within the aforementioned range, which can meet the battery energy density requirements while also having good lithium ion transmission capabilities.
[0054] According to the present invention, preferably, the positive electrode slurry and the negative electrode slurry further independently include a conductive agent, a binder and a solvent.
[0055] According to the present invention, preferably, the conductive agent is selected from at least one of conductive carbon black, carbon nanotubes and graphene.
[0056] According to the present invention, preferably, the binder is selected from polyvinylidene fluoride (PVDF) binders, preferably PVDF binders with a weight average molecular weight of 600,000-1.3 million g / mol. For example, the positive electrode binder can be a PVDF 5130 binder with a weight average molecular weight of 1.2 million g / mol, and the negative electrode binder can be a PVDF 6020 binder with a weight average molecular weight of 680,000 g / mol.
[0057] According to the present invention, preferably, the solvent is N-methylpyrrolidone (NMP).
[0058] In the present invention, the conductive agent, binder and solvent in the positive electrode slurry and the conductive agent, binder and solvent in the negative electrode slurry may be the same conductive agent, binder and solvent, or different conductive agent, binder and solvent may be used.
[0059] According to the present invention, preferably, based on the total weight (total weight of powder) of the modified lithium nickel cobalt manganese oxide, the conductive agent and the binder, in the positive electrode slurry, the content of the modified lithium nickel cobalt manganese oxide is 92-98wt%, the content of the conductive agent is 1-4wt%, and the content of the binder is 1-4wt%.
[0060] According to the present invention, preferably, based on the total weight (total weight of powder) of the nano-silicon-based negative electrode material, the conductive agent and the binder, in the negative electrode slurry, the content of the nano-silicon-based negative electrode material is 92-98wt%, the content of the conductive agent is 1-4wt%, and the content of the binder is 1-4wt%.
[0061] According to the present invention, preferably, the viscosity of the positive electrode slurry at 25-35° C. is 3500-5500 mPa·s.
[0062] According to the present invention, preferably, the viscosity of the negative electrode slurry at 25-35° C. is 3000-5000 mPa·s.
[0063] According to the present invention, preferably, based on the total weight of the positive electrode slurry, the total content (solid content) of the modified lithium nickel cobalt manganese oxide, the conductive agent and the binder is 65-77 wt %.
[0064] According to the present invention, preferably, based on the total weight of the negative electrode slurry, the total content (solid content) of the nano-silicon-based negative electrode material, the conductive agent and the binder is 45-55wt%.
[0065] According to the present invention, preferably, the average thickness of the positive electrode sheet is 82-95 μm, and the compaction density is 3.2-3.6 g / cm 3 .
[0066] According to the present invention, preferably, the average thickness of the negative electrode sheet is 100-110 μm, and the compaction density is 1.35-1.65 g / cm 3 .
[0067] According to the present invention, preferably, the diaphragm is a PE / PP / PE diaphragm with polyvinylidene fluoride (PVDF) on the surface, preferably a PE / PP / PE diaphragm with PVDF on the upper and lower surfaces. The PE / PP / PE diaphragm is a three-layer composite structure film composed of polyethylene (PE), polypropylene (PP) and polyethylene (PE), which combines the advantages of PP film and PE film, has good mechanical strength and higher safety. In the present invention, the weight average molecular weight of PE in the PE / PP / PE diaphragm is 200,000-350,000 g / mol, and the weight average molecular weight of PP is 350,000-800,000 g / mol.
[0068] Since PE / PP / PE separators are coated with PVDF on both sides, they can easily form molecular bonds with the PVDF in the positive and negative electrodes. The clamp pressure and temperature can be appropriately reduced, and the formation time can be shortened to reduce the reaction between the electrolyte and the positive and negative electrode surfaces during formation, thereby achieving the purpose of increasing the adhesion between the positive and negative electrodes and the separator while reducing the internal resistance of the battery, preventing battery deformation, and improving the initial efficiency and electrical performance of the battery.
[0069] According to the present invention, preferably, the weight average molecular weight of the PVDF covered on both sides of the PE / PP / PE separator is 500,000-1,000,000 g / mol.
[0070] According to the present invention, preferably, the total thickness of the separator is 12-20 μm.
[0071] According to the present invention, preferably, the thickness of the polyvinylidene fluoride covered on the surface of the PE / PP / PE separator is 1-4 μm.
[0072] According to the present invention, preferably, the electrolyte comprises an organic solvent, a lithium salt and an additive.
[0073] According to the present invention, preferably, based on the total weight of the electrolyte, the content of the organic solvent in the electrolyte is 75-85 wt %.
[0074] According to the present invention, preferably, the organic solvent is selected from at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethyl propionate and propyl propionate, preferably a mixture of EC, PC, EMC and DEC.
[0075] According to the present invention, preferably, the weight ratio of EC, PC, DEC and EMC is (15-20): (8-12): (33-40): (12-18). The electrolyte can reduce the viscosity of the electrolyte at low temperatures by reducing the content of EC with high melting point and high viscosity, and appropriately increasing the content of PC with low melting point, etc., and limiting the weight ratio of EC, PC, DEC and EMC to this range.
[0076] Further, the weight ratio of EC, PC, DEC and EMC is (16-18):(9-11):(36-38):(14-16).
[0077] According to the present invention, preferably, based on the total weight of the electrolyte, the content of the lithium salt in the electrolyte is 12-15 wt %.
[0078] According to the present invention, preferably, the lithium salt is selected from at least one of LiPF6, LiTFSI and LiFSI, preferably LiPF6.
[0079] According to the present invention, preferably, the additive is selected from at least one of fluoroethylene carbonate (FEC), lithium difluorophosphate (LiPO2F2), lithium dioxalatoborate (C4BLiO8), tris(trimethylsilyl)borate (TMSB), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), lithium tetrafluoroborate (LiBF) and lithium difluorooxalatoborate (LiODFB).
[0080] Furthermore, the additive is a mixture of TMSB, FEC and VC. TMSB and FEC are added to the electrolyte, both of which have strong antioxidant properties, and form stable, dense and thin CEI films and SEI films on the surfaces of the positive and negative electrodes respectively, while reducing the electrode surface impedance, reducing the reaction rate of the electrolyte with the positive and negative electrode surfaces when the battery is overcharged, thereby improving the safety performance of the battery; the VC additive in the electrolyte can undergo free radical polymerization on the surface of the carbon negative electrode, thereby effectively inhibiting the co-insertion reaction of the solvent molecules, and at the same time has no side effects on the positive electrode, has good high and low temperature performance and anti-flatulence function, and can improve the capacity and cycle life of the battery.
[0081] According to the present invention, preferably, based on the total weight of the electrolyte, in the electrolyte, the content of TMSB is 0.1-0.5wt%, the content of FEC is 1-5wt%, and the content of VC is 0.1-0.5wt%.
[0082] Furthermore, based on the total weight of the electrolyte, in the electrolyte, the content of TMSB is 0.2-0.4wt%; the content of FEC is 2-4wt%; and the content of VC is 0.2-0.4wt%.
[0083] According to the present invention, preferably, based on the total weight of the modified lithium nickel cobalt manganese oxide, the amount of the electrolyte is 30-40wt%.
[0084] According to a preferred embodiment of the present invention, the battery cell comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein,
[0085] The positive electrode sheet comprises modified nickel cobalt manganese oxide, and the modified nickel cobalt manganese oxide comprises core-shell type nickel cobalt manganese oxide and a boron-containing compound coated on the surface of the core-shell type nickel cobalt manganese oxide; wherein the content of nickel element in the core-shell type nickel cobalt manganese oxide is gradually reduced from the inside to the outside, the content of cobalt element is evenly distributed from the inside to the outside, and the content of manganese element is gradually increased from the inside to the outside;
[0086] The negative electrode sheet comprises a nano-silicon-based negative electrode material, which is a mixture of a silicon-oxygen material and graphite; wherein, based on the total weight of the nano-silicon-based negative electrode material, the content of the graphite is 82-88wt%; the silicon-oxygen material comprises silicon oxide and a carbon coating layer coated on the surface of the silicon oxide, and the silicon oxide comprises a SiO2 matrix and nano-silicon crystal particles uniformly distributed in the SiO2 matrix.
[0087] The diaphragm is a PE / PP / PE diaphragm with polyvinylidene fluoride (PVDF) covered on the surface;
[0088] The electrolyte includes an organic solvent, a lithium salt and an additive.
[0089] The active material of the positive electrode sheet adopts the core-shell type nickel cobalt manganese oxide positive electrode material coated with boron element on the surface of the present invention, the active material of the negative electrode sheet adopts the nano silicon-based negative electrode material of the present invention, the diaphragm adopts the PVDF-coated PE / PP / PE diaphragm of the present invention, and the electrolyte adopts the low-temperature and safe electrolyte of the present invention. Such a specific combination of materials greatly improves the low-temperature and safety performance of the battery.
[0090] The second aspect of the present invention provides a method for preparing a battery cell, the method comprising: winding a positive electrode sheet, a negative electrode sheet and a separator into an electrode group, and injecting an electrolyte to prepare the battery cell; wherein,
[0091] The positive electrode sheet comprises modified nickel cobalt manganese oxide, wherein the modified nickel cobalt manganese oxide comprises core-shell type nickel cobalt manganese oxide and a boron-containing compound coated on the surface of the core-shell type nickel cobalt manganese oxide, wherein the content of nickel in the core-shell type nickel cobalt manganese oxide gradually decreases from the inside to the outside, the content of cobalt is evenly distributed from the inside to the outside, and the content of manganese increases from the inside to the outside;
[0092] The negative electrode sheet comprises a nano-silicon-based negative electrode material, which is a mixture of a silicon-oxygen material and graphite; wherein, based on the total weight of the nano-silicon-based negative electrode material, the content of the graphite is 82-88wt%; the silicon-oxygen material comprises silicon oxide and a carbon coating layer coated on the surface of the silicon oxide, and the silicon oxide comprises a SiO2 matrix and nano-silicon crystal particles uniformly distributed in the SiO2 matrix.
[0093] In the preparation method of the battery cell in the second aspect of the present invention, the types and amounts of the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte are exactly the same as those in the battery cell described in the first aspect of the present invention. In order to avoid repetition, the present invention will not be described in detail in the second aspect, and those skilled in the art should not understand it as a limitation of the present invention.
[0094] According to the present invention, preferably, the method for preparing the positive electrode sheet comprises: mixing the modified lithium nickel cobalt manganese oxide, a conductive agent, a binder and a solvent to obtain a positive electrode slurry, then coating the positive electrode slurry on the surface of a positive electrode collector, and then rolling and slitting to obtain the positive electrode sheet.
[0095] According to the present invention, preferably, the method for preparing the negative electrode sheet comprises: mixing the nano-silicon-based negative electrode material, a conductive agent, a binder and a solvent to obtain a negative electrode slurry, then coating the negative electrode slurry on the surface of a negative electrode collector, and then rolling and slitting to obtain the negative electrode sheet.
[0096] According to a specific embodiment of the present invention, the preparation method of the positive electrode sheet comprises: adding a binder powder to an N-methylpyrrolidone solvent to prepare a glue having a binder concentration of 5-10wt%, and then sequentially adding a conductive agent and a modified nickel cobalt manganese oxide to the glue, and after stirring evenly, adjusting the viscosity to 3500-5500mPa·s with N-methylpyrrolidone, and adjusting the solid content to 65-77wt%, to obtain a positive electrode slurry, and then coating the positive electrode slurry on a positive electrode current collector, rolling and slitting, and finally obtaining a positive electrode sheet.
[0097] According to a specific embodiment of the present invention, the preparation method of the negative electrode sheet comprises: adding a binder powder into an N-methylpyrrolidone solvent to prepare a glue having a binder concentration of 5-10wt%, then sequentially adding a conductive agent and a nano-silicon-based negative electrode material into the glue, and after stirring evenly, adjusting the viscosity to 3000-5000mPa·s and the solid content to 45-55wt% with N-methylpyrrolidone to obtain a negative electrode slurry, and then applying the negative electrode slurry onto a negative electrode current collector, rolling and slitting, and finally obtaining a negative electrode sheet.
[0098] A third aspect of the present invention provides a battery cell prepared by the preparation method provided by the present invention.
[0099] A fourth aspect of the present invention provides a soft-pack lithium-ion battery, the battery comprising the battery cell provided by the present invention.
[0100] According to the present invention, preferably, the method for preparing the battery comprises: encapsulating the battery core using an aluminum-plastic shell, and then performing formation, final sealing and capacity separation to obtain the soft-pack lithium-ion battery.
[0101] According to the present invention, preferably, the battery has a 1C discharge capacity of greater than or equal to 60% at -40°C, and a capacity retention rate of greater than or equal to 90% after 500 cycles at room temperature.
[0102] A fifth aspect of the present invention provides an application of the soft-pack lithium-ion battery provided by the present invention as a low-temperature mobile power source.
[0103] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, unless otherwise specified, all are conventional methods; the reagents and materials used, unless otherwise specified, can be obtained from commercial channels. The determination methods involved in each example and comparative example are as follows:
[0104] Determination of element content: The particles are cut by focused ion beam (FIB) to obtain the required cross-section, and the concentration changes of nickel / cobalt / manganese from the center to the surface of the particles can be obtained from the line scan results of the EPMA instrument;
[0105] Particle size determination: weigh 5g of sample, accurate to 0.0001g, and measure with a laser particle size analyzer;
[0106] Specific surface area determination: weigh 10g of sample, accurate to 0.0001g, analyze with NOVA2000e specific surface area tester, and determine according to the static capacity method;
[0107] Normal temperature capacity test: At an indoor ambient temperature of 20℃-25℃, use a battery charge and discharge tester to charge the battery in a fully discharged state at a constant current of 0.2C to 4.2V, then switch to constant voltage charging. Stop charging when the charging current is less than 0.02C. After leaving it for 1h, discharge the battery at a current of 0.2C to 2.5V, and measure the battery's 0.2C discharge capacity;
[0108] Low temperature capacity test: Place the fully charged battery in a low temperature box at -40°C for 8 hours, then discharge it at 1C constant current to 2.5V cut-off at the same temperature, and measure the percentage of discharge capacity to initial capacity.
[0109] Cycle performance test: At an indoor ambient temperature of 20℃-25℃, use a battery charge and discharge tester to charge the battery at 0.5C constant current and constant voltage with a cut-off voltage of 4.2V, a cut-off current of 0.05C, and a constant current discharge with a cut-off voltage of 2.5V for 500 cycles to determine the battery capacity retention rate;
[0110] Safety test: The battery is overcharged, over-discharged, squeezed, recharged, hot-boxed and short-circuited to test whether it can catch fire or explode.
[0111] In the following examples, the modified lithium nickel cobalt manganese oxide was purchased from GEM Materials Co., Ltd., and the silicon oxide material and artificial graphite were purchased from Shanghai Shanshan Technology Co., Ltd.
[0112] The following examples are used to illustrate the preparation of soft-pack lithium-ion batteries.
[0113] Example 1
[0114] Positive electrode active material modified nickel cobalt manganese oxide (L-7512B), wherein:
[0115] The modified nickel cobalt manganese oxide is a core-shell type nickel cobalt manganese oxide with a boron-containing compound boron trioxide coated on the surface. 50 The particle size is 10.5 μm and the specific surface area is 1.53 m 2 / g; based on the total weight of the modified nickel cobalt manganese oxide, the content of boron is 4wt%. Among them, the distance from the core to the core surface of the core-shell type nickel cobalt manganese oxide is 3μm, and the distance from the core surface to the shell surface is 2μm;
[0116] Based on the total weight of nickel, cobalt and manganese in the core-shell type nickel cobalt manganese oxide, the nickel content from the core to the core surface of the core-shell type nickel cobalt manganese oxide decreases from 81wt% to 69wt%, with a content change rate of 4wt% / μm; the manganese content increases from 10wt% to 22wt%, with a content change rate of 4wt% / μm. From the core surface to the shell surface of the core-shell type nickel cobalt manganese oxide, the nickel content decreases from 69wt% to 58wt%, with a content change rate of about 5.5wt% / μm; the manganese content increases from 22wt% to 33wt%, with a content change rate of 5.5wt% / μm. The cobalt content is evenly distributed at 9wt%.
[0117] Negative electrode active material Nano silicon-based negative electrode material, wherein:
[0118] Negative electrode active material The nano-silicon-based negative electrode material is made by grinding and mixing silicon oxide material (S1550) and artificial graphite (QCG-X1); based on the total weight of the nano-silicon-based negative electrode material, the content of artificial graphite is 86wt%; the gram capacity of artificial graphite is 360mAh / g; the nano-silicon-based negative electrode material D 50 The particle size is 11.8 μm and the specific surface area is 8.4 m 2 / g. The gram capacity of the silicon-oxygen material is 1450mAh / g, the average particle size of the nano-silicon crystal particles in the silicon-oxygen material is 4nm, and the average particle size of the SiO2 matrix is 7μm; based on the total weight of the silicon-oxygen material, the content of the nano-silicon crystal particles is 27.4wt%, and the content of the SiO2 matrix is 69.6wt%; the thickness of the amorphous carbon-carbon coating layer is 8nm.
[0119] (1) Preparation of positive electrode sheet:
[0120] The 5130 binder powder with a weight average molecular weight of 1.2 million g / mol was added to N-methylpyrrolidone solvent and stirred at high speed for 2.5 hours to prepare a glue with a binder concentration of 8wt%. Then, the conductive agent SP and modified nickel cobalt manganese oxide were added to the glue in sequence. After stirring for 4.5 hours, the viscosity of the slurry at 25°C was adjusted to 5000mPa·s with N-methylpyrrolidone, and the solid content was adjusted to 70wt% to obtain a positive electrode slurry. The positive electrode slurry was then passed through a 200-mesh sieve and coated on an aluminum foil with a thickness of 16μm. The coating surface density was 125±2.5g / cm 2 After coating and drying, roll to a thickness of 86±2μm and a compaction density of 3.45g / cm 2 ; The rolled electrode is then striped and the tabs are welded to obtain the positive electrode; wherein,
[0121] Based on the total weight of the modified lithium nickel cobalt manganese oxide, the conductive agent SP and the 5130 binder, the content of the modified lithium nickel cobalt manganese oxide is 96wt%, the content of the conductive agent SP is 2.5wt%, and the content of the 5130 binder is 1.5wt%.
[0122] (2) Preparation of negative electrode sheet:
[0123] The 6020 binder powder with a weight average molecular weight of 680,000 g / mol was added to the N-methylpyrrolidone solvent and stirred at high speed for 2.5 hours to prepare a glue with a binder concentration of 8wt%. Then, the conductive agent SP and the nano-silicon-based negative electrode material were sequentially added to the glue. After stirring for 4.5 hours, the viscosity of the slurry at 25°C was adjusted to 4000mPa·s with N-methylpyrrolidone, and the solid content was adjusted to 55wt% to obtain the negative electrode slurry. Then, the negative electrode slurry was passed through a 200-mesh sieve and coated on a copper foil with a thickness of 7μm. The coating surface density was 74±1.5g / cm 2 After coating and drying, roll to a thickness of 106±2μm and a compaction density of 1.52g / cm 2 ; The rolled electrode is then striped and the tabs are welded to obtain a negative electrode; wherein,
[0124] Based on the total weight of the nano silicon-based negative electrode material, the conductive agent SP and the 6020 binder, the content of the nano silicon-based negative electrode material is 98wt%, the content of the conductive agent SP is 1wt%, and the content of the 6020 binder is 1wt%.
[0125] (3) The diaphragm is a PE / PP / PE diaphragm (weight average molecular weight of PE is 300,000 g / mol, weight average molecular weight of PP is 700,000 g / mol) coated on both sides with PVDF (weight average molecular weight of 800,000 g / mol), with a total thickness of 15 μm and a single-side coating thickness of 3 μm.
[0126] (4) Preparation of electrolyte:
[0127] The solvent is a mixed solvent of EC, PC, DEC and EMC in a weight ratio of 17:10:37:15, the electrolyte is LiPF6, and the additive is a mixture of TMSB, FEC and VC. Among them, based on the total weight of the electrolyte, the content of the solvent is 82.7wt%, the content of LiPF6 is 13.7wt%, the content of TMSB is 0.3wt%, the content of FEC is 3wt%, and the content of VC is 0.3wt%.
[0128] (5) Preparation of batteries: The positive / negative electrode sheets and separators are wound into an electrode group, and then the electrolyte is injected, and packaging, formation, final sealing and capacity division are performed to complete the production to obtain a soft-pack lithium-ion battery; wherein the amount of electrolyte used is 34wt% based on the total weight of the modified lithium nickel cobalt manganese oxide.
[0129] Example 2
[0130] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the powder composition ratios of the positive and negative electrodes were different. Specifically, based on the total weight of the modified nickel cobalt manganese oxide (same as Example 1), the conductive agent SP (same as Example 1) and the 5130 binder (same as Example 1), the content of the modified nickel cobalt manganese oxide was 95wt%, the content of the conductive agent SP was 2wt%, and the content of the 5130 binder was 3wt%; based on the total weight of the nano-silicon-based negative electrode material, the conductive agent SP and the 6020 binder, the content of the nano-silicon-based negative electrode material (same as Example 1) was 96.5wt%, the content of the conductive agent SP was 1.5wt%, and the content of the 6020 binder (same as Example 1) was 2wt%. A soft-pack lithium-ion battery was prepared.
[0131] Example 3
[0132] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that modified nickel cobalt manganese oxide with different boron content was selected. Specifically, modified nickel cobalt manganese oxide with a grade of L-7013B was selected, and the boron content was 13 wt% based on the total weight of the modified nickel cobalt manganese oxide to obtain a soft-pack lithium-ion battery.
[0133] Example 4
[0134] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the particle size and specific surface area of the nano-silicon-based negative electrode material were different. 50 The particle size is 13.7 μm and the specific surface area is 4.7 m 2 / g of nano silicon-based negative electrode material; wherein the gram capacity of the silicon-oxygen material (brand name S1500) is 1350mAh / g, the average particle size of the nano silicon crystal particles in the silicon-oxygen material is 6nm, and the average particle size of the SiO2 matrix is 8μm; based on the total weight of the silicon-oxygen material, the content of the nano silicon crystal particles is 27.4wt%, and the content of the SiO2 matrix is 69.6wt%; the thickness of the amorphous carbon-carbon coating layer is 8nm; the gram capacity of the artificial graphite is 360mAh / g. A soft-pack lithium-ion battery is obtained.
[0135] Example 5
[0136] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the coating amounts of the positive electrode slurry and the negative electrode slurry were different. Specifically, when preparing the positive electrode sheet, the surface density of the positive electrode slurry coated on the aluminum foil was 140±2.5 g / cm 2 When preparing the negative electrode sheet, the surface density of the negative electrode slurry coated on the copper foil is 85±1.5g / cm 2 ; A soft-pack lithium-ion battery is prepared.
[0137] Example 6
[0138] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the powder composition ratios of the positive and negative electrodes were different. Specifically, when preparing the positive electrode, the total weight of the modified nickel cobalt manganese oxide (same as Example 1), the conductive agent SP (same as Example 1) and the 5130 binder (same as Example 1) was used as a reference, and the content of the modified nickel cobalt manganese oxide was 90wt%, the content of the conductive agent SP was 5wt%, and the content of the 5130 binder was 5wt%; when preparing the negative electrode, the total weight of the nano-silicon-based negative electrode material, the conductive agent SP and the 6020 binder was used as a reference, and the content of the nano-silicon-based negative electrode material (same as Example 1) was 90wt%, the content of the conductive agent SP was 5wt%, and the content of the 6020 binder (same as Example 1) was 5wt%. A soft-pack lithium-ion battery was prepared.
[0139] Example 7
[0140] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the average thickness and compaction density of the positive and negative electrode sheets were different. Specifically, when preparing the positive electrode sheet, the positive electrode sheet was rolled to a thickness of 100±2 μm after coating and drying, and a compaction density of 3.65 g / cm 2 ; When preparing the negative electrode sheet, after coating and drying, roll it to a thickness of 115±2μm and a compaction density of 1.65g / cm 2 . A soft-pack lithium-ion battery is obtained.
[0141] Example 8
[0142] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that a different separator was used. Specifically, a PP / PE / PP composite base film with a thickness of 16 μm was used as the separator. A soft-pack lithium-ion battery was prepared.
[0143] Example 9
[0144] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the thickness of the polyvinylidene fluoride coated on the surface of the PE / PP / PE separator was different, the single-side coating thickness was 8 μm, and the total thickness of the separator was 20 μm. A soft-pack lithium-ion battery was prepared.
[0145] Example 10
[0146] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the composition of the solvent in the electrolyte was different. Specifically, the EMC in the solvent was replaced with an equal weight of DMC to obtain a soft-pack lithium-ion battery.
[0147] Embodiment 11
[0148] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the amount of EC in the electrolyte was increased and the amount of PC was reduced. Specifically, the solvent in the electrolyte was a mixed solvent with a weight ratio of EC, PC, DEC and EMC of 23:4:37:15. A soft-pack lithium-ion battery was prepared.
[0149] Example 12
[0150] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the ratios of TMSB, FEC and VC in the additives were different. Specifically, based on the total weight of the electrolyte, the content of TMSB was 1wt%, the content of FEC was 2wt%, and the content of VC was 0.6wt%. A soft-pack lithium-ion battery was prepared.
[0151] Example 13
[0152] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the distribution of elements in the core-shell type nickel cobalt manganese oxide in the modified nickel cobalt manganese oxide was different. Specifically, the modified nickel cobalt manganese oxide with the grade of L-7012B was selected. 50 The particle size is 11.2 μm and the specific surface area is 0.71 m 2 / g. Among them, the distance from the core to the core surface of the core-shell type nickel cobalt manganese oxide is 3.1μm, and the distance from the core surface to the shell surface is 2.2μm;
[0153] Based on the total weight of nickel, cobalt and manganese in the core-shell type nickel cobalt manganese lithium, the nickel content from the core to the core surface of the core-shell type nickel cobalt manganese lithium is reduced from 72wt% to 54wt%, and the content change rate is 5.8wt% / μm; the manganese content is increased from 19wt% to 37wt%, and the content change rate is 5.8wt% / μm. From the core surface to the shell surface of the core-shell type nickel cobalt manganese lithium, the nickel content is reduced from 54wt% to 43wt%, and the content change rate is about 5wt% / μm; the manganese content is increased from 37wt% to 48wt%, and the content change rate is 5wt% / μm. The content of cobalt is evenly distributed at 9wt%. A soft-pack lithium-ion battery is prepared.
[0154] Embodiment 14
[0155] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the type of lithium salt in the electrolyte was different. Specifically, LiPF6 was replaced with an equal weight of LiTFSI to obtain a soft-pack lithium-ion battery.
[0156] Comparative Example 1
[0157] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the active material of the negative electrode sheet was different. Specifically, when preparing the negative electrode sheet, graphite was used instead of an equal weight of the nano-silicon-based negative electrode material to obtain a soft-pack lithium-ion battery.
[0158] Comparative Example 2
[0159] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the active material of the positive electrode sheet was different. Specifically, when preparing the positive electrode sheet, a LiNi 0.8 Co 0.15 Al 0.05 The NCA shown in O2 replaces an equal weight of modified lithium nickel cobalt manganese oxide to obtain a soft-pack lithium-ion battery.
[0160] Comparative Example 3
[0161] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the active materials of the positive electrode sheet and the negative electrode sheet were different. Specifically, when preparing the positive electrode sheet, a LiNi 0.8 Co 0.15 Al 0.05 The NCA shown in O2 replaces the modified nickel cobalt manganese oxide of equal weight, and when preparing the negative electrode sheet, graphite replaces the nano silicon-based negative electrode material of equal weight to obtain a soft-pack lithium ion battery.
[0162] Comparative Example 4
[0163] A soft-pack lithium-ion battery was prepared according to the method of Example 1, except that the content of graphite in the nano-silicon-based negative electrode material was different. Specifically, based on the total weight of the nano-silicon-based negative electrode material, the content of graphite in the nano-silicon-based negative electrode material was 60wt%. Thus, a soft-pack lithium-ion battery was prepared.
[0164] Test Case
[0165] The soft-pack lithium-ion batteries prepared in each embodiment and comparative example were subjected to normal temperature capacity test, low temperature capacity test, cycle performance test and safety test. The results of the discharge capacity of the battery in the normal temperature capacity test, the percentage of the discharge capacity to the initial capacity in the low temperature capacity test, the battery capacity retention rate in the cycle performance test and whether there was fire and explosion in the safety test are shown in Table 1. The low temperature discharge curves of the soft-pack lithium-ion batteries prepared in Example 1 of the present invention and Comparative Examples 1-3 are shown in Table 1. Figure 1 , normal temperature cycle curve see Figure 2 .
[0166] Table 1
[0167]
[0168]
[0169] Comparative Example 1 changes the type of negative electrode active material, Comparative Example 2 changes the type of positive electrode active material, and Comparative Example 3 changes the types of both positive and negative electrode active materials. Figure 1 It can be seen that compared with Comparative Examples 1-3, the percentage of low-temperature discharge capacity of the battery obtained in Example 1 to the initial capacity is significantly higher, indicating that the battery prepared by using the positive electrode active material and the negative electrode active material of the present invention still has excellent low-temperature discharge performance after low-temperature storage; Figure 2 It can be seen that compared with Comparative Examples 1-3, the capacity retention rate of the battery obtained in Example 1 after 500 cycles at room temperature is significantly higher than that of Comparative Examples 1-3, indicating that the battery prepared using the positive electrode active material and the negative electrode active material of the present invention has good cycle performance. In addition, Comparative Example 4 reduces the content of graphite in the nano-silicon-based negative electrode material. Compared with Example 1, the capacity retention rate of the battery obtained in Comparative Example 4 after 500 cycles at room temperature is significantly reduced, indicating that the content of graphite in the nano-silicon-based negative electrode material has a great influence on the cycle performance of the battery. The battery obtained in Example 1 of the present invention has good low-temperature discharge performance and room temperature cycle performance, and has excellent safety performance.
[0170] In addition, Example 3 changes the content of boron in the modified lithium nickel cobalt manganese oxide, Example 4 changes the particle size and specific surface area of the nano-silicon-based negative electrode material, Example 5 changes the coating amount of the positive electrode slurry and the negative electrode slurry when preparing the positive and negative electrode sheets, Example 6 changes the powder composition ratio of the positive and negative electrode sheets, Example 7 changes the average thickness and compaction density of the positive and negative electrode sheets, Example 8 uses a different diaphragm, Example 9 has a different thickness of polyvinylidene fluoride covered on the surface of the diaphragm, Example 10 changes the solvent composition in the electrolyte, Example 11 changes the component content in the electrolyte, Example 12 changes the component content in the additive, and Example 13 changes the content of the electrolyte. Example 13 uses different core-shell nickel cobalt manganese oxide lithium, and Example 14 changes the type of lithium salt in the electrolyte. Compared with Example 1, the percentage of low-temperature discharge capacity to initial capacity and the capacity retention rate of 500 cycles at room temperature of the batteries obtained in Examples 3-11 and 13 are reduced to a certain extent; the battery obtained in Example 12 not only has a reduced percentage of low-temperature discharge capacity to initial capacity and a reduced capacity retention rate of 500 cycles at room temperature, but also the battery is overcharged and explodes; although the battery obtained in Example 14 has a high percentage of low-temperature discharge capacity to initial capacity, the capacity retention rate of 500 cycles at room temperature is reduced, and the battery is overcharged and explodes. This shows that the types and properties of positive and negative active materials, the coating amount of positive and negative electrode slurries in positive and negative electrode sheets, the powder composition, thickness and compaction density of positive and negative electrode sheets, and the composition of diaphragms, electrolytes and additives jointly affect the low-temperature discharge performance, room temperature cycle performance and safety performance of the battery.
[0171] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A battery cell, characterized in that: The battery cell comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein, The positive electrode sheet comprises modified nickel cobalt manganese oxide, and the modified nickel cobalt manganese oxide comprises core-shell type nickel cobalt manganese oxide and a boron-containing compound coated on the surface of the core-shell type nickel cobalt manganese oxide; wherein the content of nickel element in the core-shell type nickel cobalt manganese oxide is gradually reduced from the inside to the outside, the content of cobalt element is evenly distributed from the inside to the outside, and the content of manganese element is gradually increased from the inside to the outside; The negative electrode sheet comprises a nano-silicon-based negative electrode material, which is a mixture of a silicon-oxygen material and graphite; wherein, based on the total weight of the nano-silicon-based negative electrode material, the content of the graphite is 82-88wt%; the silicon-oxygen material comprises silicon oxide and a carbon coating layer coated on the surface of the silicon oxide, and the silicon oxide comprises a SiO2 matrix and nano-silicon crystal particles uniformly distributed in the SiO2 matrix.
2. The battery cell according to claim 1, characterized in that: Based on the total weight of nickel, cobalt and manganese in the core-shell type nickel cobalt manganese oxide, the change rate of the nickel content from the core to the core surface of the core-shell type nickel cobalt manganese oxide is 3-5wt% / μm, and the change rate of the manganese content is 3-5wt% / μm; From the core surface to the shell surface of the core-shell type nickel cobalt lithium manganese oxide, the change rate of the nickel content is 5-6wt% / μm, and the change rate of the manganese content is 5-6wt% / μm; Preferably, the distance from the core to the core surface of the core-shell type nickel cobalt manganese oxide is 2.7-3.2 μm, and the distance from the core surface to the shell surface is 1.5-2.5 μm; Preferably, the boron-containing compound is selected from at least one of boron trioxide, boron trichloride, boron trifluoride, boric acid and sodium metaborate; Preferably, based on the total weight of the modified lithium nickel cobalt manganese oxide, the content of boron in the boron-containing compound is 2-12 wt %.
3. The battery cell according to claim 1 or 2, characterized in that: The modified lithium nickel cobalt manganese oxide D 50 The particle size is 8-12μm and the specific surface area is 0.5-2m 2 / g.
4. The battery cell according to any one of claims 1 to 3, characterized in that: The D of the nano silicon-based negative electrode material 50 The particle size is 7-13μm and the specific surface area is 5-9m 2 / g; Preferably, in the nano-silicon-based negative electrode material, the gram capacity of the graphite is 300-360 mA·h / g; Preferably, the graphite is selected from at least one of artificial graphite, natural graphite and mesophase carbon microspheres; Preferably, in the nano-silicon-based negative electrode material, the gram capacity of the silicon-oxygen material is 1250-1750 mA·h / g; Preferably, the average particle size of the nano-silicon crystal particles is 2-10 nm, and the average particle size of the SiO2 matrix is 3-8 μm; Preferably, based on the total weight of the silicon-oxygen material, the content of the nano-silicon crystal particles is 26-28wt%, and the content of the SiO2 matrix is 69-73wt%; Preferably, the carbon coating layer is amorphous carbon; Preferably, the thickness of the carbon coating layer is 8-13 nm.
5. The battery cell according to any one of claims 1 to 4, characterized in that: The positive electrode sheet is obtained by coating the positive electrode slurry including the modified lithium nickel cobalt manganese oxide on the surface of the positive electrode collector, and the negative electrode sheet is obtained by coating the negative electrode slurry including the nano silicon-based negative electrode material on the surface of the negative electrode collector; Preferably, the positive electrode slurry and the negative electrode slurry further independently include a conductive agent, a binder and a solvent; Preferably, based on the total weight of the modified lithium nickel cobalt manganese oxide, the conductive agent and the binder, in the positive electrode slurry, the content of the modified lithium nickel cobalt manganese oxide is 92-98wt%, the content of the conductive agent is 1-4wt%, and the content of the binder is 1-4wt%; Preferably, based on the total weight of the nano silicon-based negative electrode material, the conductive agent and the binder, in the negative electrode slurry, the content of the nano silicon-based negative electrode material is 92-98wt%, the content of the conductive agent is 1-4wt%, and the content of the binder is 1-4wt%; Preferably, the viscosity of the positive electrode slurry at 25-35° C. is 3500-5500 mPa·s; Preferably, the viscosity of the negative electrode slurry at 25-35° C. is 3000-5000 mPa·s; Preferably, the average thickness of the positive electrode sheet is 82-95 μm, and the compaction density is 3.2-3.6 g / cm 3 ; Preferably, the average thickness of the negative electrode sheet is 100-110 μm, and the compaction density is 1.35-1.65 g / cm 3 .
6. The battery cell according to any one of claims 1 to 5, characterized in that: The diaphragm is a PE / PP / PE diaphragm with polyvinylidene fluoride on the surface; Preferably, the total thickness of the diaphragm is 12-20 μm; Preferably, the thickness of the polyvinylidene fluoride coated on the surface of the PE / PP / PE separator is 1-4 μm; Preferably, the weight average molecular weight of the polyvinylidene fluoride is 0.5 million to 1 million g / mol.
7. The battery cell according to any one of claims 1 to 6, characterized in that: The electrolyte comprises an organic solvent, a lithium salt and an additive; Preferably, based on the total weight of the electrolyte, the content of the organic solvent in the electrolyte is 75-85wt%; Preferably, the organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl propionate and propyl propionate, preferably a mixture of ethylene carbonate, propylene carbonate, ethyl methyl carbonate and diethyl carbonate; Preferably, based on the total weight of the electrolyte, the content of the lithium salt in the electrolyte is 12-15wt%; Preferably, the lithium salt is selected from at least one of LiPF6, LiTFSI and LiFSI, preferably LiPF6; Preferably, the additive is selected from at least one of fluoroethylene carbonate, lithium difluorophosphate, lithium dioxalatoborate, tris(trimethylsilyl)borate, vinylene carbonate, vinylethylene carbonate, lithium tetrafluoroborate and lithium difluorooxalatoborate, preferably a mixture of tris(trimethylsilyl)borate, fluoroethylene carbonate and vinylene carbonate; Preferably, based on the total weight of the electrolyte, in the electrolyte, the content of tris(trimethylsilyl)borate is 0.1-0.5wt%, the content of fluoroethylene carbonate is 1-5wt%, and the content of vinylene carbonate is 0.1-0.5wt%.
8. A method for preparing a battery cell, characterized in that: The preparation method comprises: winding a positive electrode sheet, a negative electrode sheet and a separator into an electrode group, and injecting an electrolyte to obtain the battery cell; wherein, The positive electrode sheet comprises modified nickel cobalt manganese oxide, and the modified nickel cobalt manganese oxide comprises core-shell type nickel cobalt manganese oxide and a boron-containing compound coated on the surface of the core-shell type nickel cobalt manganese oxide; wherein the content of nickel element in the core-shell type nickel cobalt manganese oxide is gradually reduced from the inside to the outside, the content of cobalt element is evenly distributed from the inside to the outside, and the content of manganese element is gradually increased from the inside to the outside; The negative electrode sheet comprises a nano-silicon-based negative electrode material, which is a mixture of a silicon-oxygen material and graphite; wherein, based on the total weight of the nano-silicon-based negative electrode material, the content of the graphite is 82-88wt%; the silicon-oxygen material comprises silicon oxide and a carbon coating layer coated on the surface of the silicon oxide, and the silicon oxide comprises a SiO2 matrix and nano-silicon crystal particles uniformly distributed in the SiO2 matrix.
9. The preparation method according to claim 8, characterized in that: The preparation method of the positive electrode sheet comprises: mixing the modified lithium nickel cobalt manganese oxide, a conductive agent, a binder and a solvent to obtain a positive electrode slurry, then coating the positive electrode slurry on the surface of a positive electrode current collector, and then rolling and slitting to obtain the positive electrode sheet; Preferably, the preparation method of the negative electrode sheet comprises: mixing the nano silicon-based negative electrode material, a conductive agent, a binder and a solvent to obtain a negative electrode slurry, then coating the negative electrode slurry on the surface of a negative electrode collector, and then rolling and slitting to obtain the negative electrode sheet.
10. A battery cell prepared by the preparation method according to claim 8 or 9.
11. A soft-pack lithium-ion battery, characterized in that: The battery comprises the battery cell according to any one of claims 1 to 7 and 10; Preferably, the battery has a 1C discharge capacity of greater than or equal to 60% at -40°C, and a capacity retention rate of greater than or equal to 90% after 500 cycles at room temperature.
12. Use of the soft-pack lithium-ion battery according to claim 11 as a low-temperature mobile power source.
Citation Information
Patent Citations
Nickel cobalt lithium manganate composite positive electrode material and preparation method thereof as well as lithium ion battery
CN108777295A
Low-temperature lithium-ion battery
CN109888368A
Lithium ion battery positive plate, preparation method thereof and lithium ion battery
CN113948673A
21700 lithium ion battery and preparation method thereof
CN114695942A
Lithium-ion battery
US20180351209A1